2015
DOI: 10.1099/vir.0.000032
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein overcomes H2O2-induced apoptosis by downregulating p14 expression via DNA methylation

Abstract: Infection with hepatitis C virus (HCV) is characterized by systemic oxidative stress that is caused by either viral core protein or chronic inflammation. It is well recognized that reactive oxygen species (ROS) such as H 2 O 2 can induce apoptotic cell death and can therefore function as anti-tumorigenic species. However, the detailed mechanisms by which ROS induce apoptotic cell death and HCV copes with the oxidative conditions are largely unknown. In the present study, we found that H 2 O 2 induced apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…H 2 O 2 treatment increased the levels of protein p14 and induced the ubiquitin-dependent degradation of mouse double minute 2 (MDM2) protein with a subsequent reduction of MDM2-p53 interaction, accumulation of p53 and activation of p53-dependent apoptotic pathways. In this model, HCV Core decreased p14 expression, resulting in inactivation of the p14-MDM2-p53 pathway [41].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…H 2 O 2 treatment increased the levels of protein p14 and induced the ubiquitin-dependent degradation of mouse double minute 2 (MDM2) protein with a subsequent reduction of MDM2-p53 interaction, accumulation of p53 and activation of p53-dependent apoptotic pathways. In this model, HCV Core decreased p14 expression, resulting in inactivation of the p14-MDM2-p53 pathway [41].…”
Section: Discussionmentioning
confidence: 94%
“…There are only a few reports that investigated adaptive mechanisms of HCV-infected liver cells [21,41]. Seo et al, reported that HCV Core expressing HepG2 and Huh-7.5 cells are more resistant to hydrogen peroxide (H 2 O 2 )-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that both events involve reactive oxygen species as mediators. In addition, ROS suppress the expression of p14 protein that is implicated in induction of the proapoptotic p53-Mdm2 pathway [210]. Additional input into the survival of HCV-infected cells under chronic mitochondrial dysfunction comes from the induction of mitophagy, an event of autophagosomal removal of damaged mitochondria [211].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Several studies note that tumor suppressor p53 may be a target of the core. The proapoptotic effect of ROS is abolished when the p14–MDM2 (mouse double minute 2)-p53 pathway is repressed by the core through p14 promoter hypermethylation 70. Elevated sirt1 expression is another mechanism of p53 attenuation 71…”
Section: Hepatocyte Apoptosis and Viral Hepatitismentioning
confidence: 99%